Interaction between folic acid and brain vascular accident: an integrative literature review (Research, Society and Development, 2020)
The study aimed to carry out a systematic review in order to correlate vitamin B9 (folic acid) deficiency with the presence of Stroke - Stroke. This is a study of systematic literature review, which followed guidelines found in scientific works. The question that guided the review was: “Can the use of folic acid prevent stroke?” Observational studies have reported that the use of folic acid promotes beneficial effects in the protection and prevention of some diseases, among them ischemic stroke - stroke. Studies indicate that a 10% lower risk of stroke and a 4% lower risk of cardiovascular disease with folic acid supplementation. In addition, it suggests that lower levels of serum homocysteine are correlated with a lower incidence of cardiovascular disease. Supplementation with folic acid and B12 can reduce the risk of the first stroke. Therefore, more in-depth studies are essential as to its beneficial effects, treatment or prevention of stroke.